Higher frequency of secretor phenotype in O blood group – its benefits in prevention and/or treatment of some diseases - Mohamad Salih Jaff (Dove Medical Press, 2010)
Mohamad Salih JaffPathology Department, Hawler Medical University (Formerly Salahaddin University), Erbil, Kurdistan Region, IraqAbstract: ABO blood groups and secretor status are important in clinical and forensic medicine and in relation to some diseases. There are geographic and racial differences in their frequencies, but the frequency of secretor status in different ABO blood group systems has not been determined yet. Therefore, the aim of this study was mainly to determine this point. Blood and saliva from 762 randomly selected apparently healthy adult individuals (480 men and 282 women) were examined to determine their ABO and Rhesus blood groups by standard conventional methods, and their secretor status by using Lewis blood grouping and/or hemagglutination inhibition test of saliva. Results showed that 76.1% of the study population were ABH blood group antigens secretors and 23.9% were nonsecretors. The frequencies of secretor status in different ABO blood groups were 70.1% in group A, 67.8% in group B, 67.9% in group AB, and 88.3% in group O. In conclusion, blood group O individuals have significantly higher frequency of secretor status than non-O blood group individuals. This finding would be beneficial to them, protecting them, at least partially, from certain malignancies or allowing them to have less aggressive disease, and this finding might be useful in enhancing further studies and research in this direction.Keywords: blood group O, ABO blood groups, secretor phenotype, frequency, malignancies, prevention and/or treatment